Effective dose of propolis extract against pain response in mice (Mus musculus) using writhing test method - Salsabilla Zamrutizahra, Chonny; Widjiastuti, Ira; Kunarti, Sri (Conservative Dentistry Journal, 2022)
Background: Odontogenic pain has a high prevalence. One of the alternative materials used as medicine in dentistry is propolis. Propolis is a mixture of natural resins containing flavonoid and phenolic acids that play a role in suppressing the pain response through COX and NF-kB inhibition mechanisms. The content of active propolis compounds is influenced by the type of bee, region, geographical conditions, climate change, seasons, and botanical sources causing different effectiveness of propolis. This is supported by several studies that show a variety of effective doses that produce an optimal analgesic effect, thus a research plan was developed to discover the effective dose of propolis extract on suppressing pain response in mice using the writhing test method. Purpose: To determine the effective dose of propolis extract towards pain response in mice. Methods: This study was conducted using the writhing test method to see the analgesic effect of propolis extract. The research sample consisted of 30 mice which were divided into five treatment groups, namely the piroxicam control group, and the propolis extract group at doses of 35 mg/kgBW, 70 mg/kgBW, 105 mg/kgBW, 140 mg/kgBW. Results: The results showed that the propolis extract dose of 70 mg/kgBW had no significant difference with the piroxicam control group, while between the doses of 35 mg/kgBW, 105 mg/kgBW, 140 mg/kgBW there was a significant difference towards the piroxicam control group. Conclusion: Propolis extract 70 mg/kgBW is the effective dose in suppressing pain response in mice